Electrochemistry of Immobilized Particles and Droplets : Experiments with Three-Phase Electrodes - Scholz, Fritz; Schröder, Uwe; Gulaboski, Rubin; Doménech-Carbó, Antonio (Springer International Publishing : Imprint: Springer, 2015)
This second edition of a successful and highly-accessed monograph has been extended by more than 100 pages. It includes an enlarged coverage of applications for materials characterization and analysis. Also a more detailed description of strategies for determining free energies of ion transfer between miscible liquids is provided. This is now possible with a "third-phase strategy" which the authors explain from theoretical and practical points of view. The book is still the only one detailing strategies for solid state electroanalysis. It also features the specific potential of the techniques to use immobilized particles (for studies of solid materials) and of immobilized droplets of immiscible liquids for the purpose of studying the three-phase electrochemistry of these liquids. This also includes studies of ion transfer between aqueous and immiscible non-aqueous liquids. The bibliography of all published papers in this field of research has been expanded from 318 to now 444 references in this second edition. Not only are pertinent references provided at the end of each chapter, but the complete list of the cited literature is also offered as a separate chapter for easy reference.